Learners' perspectives on promoting cultural literacy via an alternative assessment: a classroom approach / S. Suchithra K. Sankaran Nair, Muna Liyana Mohamad Tarmizi and Maizura Mohd Noor - K. Sankaran Nair, S. Suchithra; Mohamad Tarmizi, Muna Liyana; Mohd Noor, Maizura (Universiti Teknologi MARA, 2022)
In the 21st century learning landscape, arguably few features of teaching and learning are void of technology. Palpably, the pandemic has made technology mandatory in remote teaching and delivery of assessments are no exception. Nonetheless, the significance of devising fitting online assessments is not only fundamental to achieving course outcomes but also focal to developing 21st century skills. One such assessment that was borne out of necessity is the Virtual Cultural Exhibition (VCE). Within this backdrop, the study explores the experiences of students who planned, proposed, designed, and staged the VCE as part of an alternative assessment initiative. Specifically, this study was designed to examine how the learners perceived the alternative assessment in helping them (a) develop social responsibility and respect for global cultural identities in line with the course learning objectives, (b) develop 21st Century skills and (c) identify the challenges and issues faced by them. To accomplish these objectives, a total of 100 students from five different groups were selected. Different data collection methods (student survey and semi-structured interviews) were used, and the data were analysed using mixed method approaches. The findings reveal that although the VCE is a promising approach to develop learners' cultural literacy and promote creativity and collaboration, it is time demanding. Adjustments were made to the VCE specifically in terms of task specifications in response to the learners' feedback. This study provides a foundation for improving the design and implementation of online assessments in intercultural communication courses to promote real world skills.